Extensive Epidural Hemorrhage Associated with Thoracolumbar Disc Extrusion in French Bulldogs - Julius Underberg; Arianna Maiolini; Maja Waschk; Daniela Schweizer (Veterinary Sciences)
(1) Background: Intervertebral disc extrusion may be accompanied by extensive epidural hemorrhage (EEH) and result in spinal cord compression. EEH is more commonly seen in French Bulldogs compared to other breeds. The majority of French Bulldogs have lumbar intervertebral disc extrusion, but it is unclear if there is an association between the site of thoracolumbar disc extrusion and EEH. This retrospective study’s aim was to investigate the association and prevalence between the site of thoracolumbar intervertebral disc extrusion and EEH in French Bulldogs. (2) Methods: Thoracolumbar MRI of French Bulldogs was examined for the site of intervertebral disc extrusion and the presence, distribution, and extent of EEH. (3) Results: In 148 French Bulldogs with thoracolumbar intervertebral disc extrusion, the most common location was L4/L5 (22%), followed by L3/L4 (20%) and T13/L1 (15%), and 70.3% had EEH. The highest incidence of EEH across all thoracolumbar sites was seen at L1/L2 (84.2%), followed by L5/L6 (81.3%) and L2/L3 (72.2%). The incidence of EEH was 70.5% across all lumbar sites and 66.9% for all thoracic sites. (4) Conclusion: In this population of French Bulldogs, the prevalence of lumbar disc extrusion was high, and 70.3% had EEH. There was no significant difference between the site of thoracolumbar intervertebral disc extrusion and EEH.